CD atlas of allergies - Fireman, Philip; Fireman,Philip; Mosby-Year Book (London : Mosby, 1997)
(Producer) A comprehensive collection of allergy visuals. It incorporates all aspects of the second ed. of Atlas allergies. In addition, key pictures and integrated from: A color atlas off allergic skin disordes; and, A calor atlas of pediatric allergy.
Title disc label
CD is available at Koleksi Media, Perpustakaan HUKM
Pictorial contributors, Williams F.Jackson, Rino Cerio, John O.Warner
System requirements: Power Mac or 68040; 8MB RAM, 2MB avaible hard disk space; Systems 7.0 or above; double speed or faster CD-ROM drive; will run on systems with 8-bit col. (256 colors) but16-bit (thousands colors) is strongly recommended.
System requirements: IBM PC or compatible, minimum 66mhz 486DX2; 8MB RAM, 2MB avaible hard disk space; Windows 95; double speed or faster CD-ROM drive; will run on systems with 8-bit col.(256 colors) but 16-bit (thousands of colours) is strongly recomended.
Keywords: Hypersensitivity -- atlases -- CD-ROM